Application of Differential Equations Separate Variables in Physics - Putranti, Sri Rejeki Dwi (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2023)
Many important problems in engineering, physics and the social sciences, when formed in mathematical form, require the determination of a function that satisfies one or more derivative of an unknown function. Such an equation is called a Differential Equation. One of the differential equations we know is Newton's Law. One obvious clarification is to look at whether an unknown function depends on one or more independent variables, when only one is called a Partial Differential Equation. In this article will be discussed differential equations with separate variables (can be separated) to be able to solve in physics problems. Keywords: equation; variable; differential